The effect of perpetrator mental disorder diagnosis on perceptions of stalking - Sambrooks, Katie (2017)
Determining which behaviour warrants a label of stalking can be a difficult and subjective process. Previous studies considering the influence of perpetrator mental illness on perceptions of stalking have never specified a specific mental disorder (Kinkade, Burns, & Fuentes, 2005; Landwehr, 2016). The present study manipulated the disorder across vignettes so that the perpetrator was described as being diagnosed with depression, personality disorder, psychosis, substance misuse or had no history of mental illness. There was no significant effect of diagnosis on perceptions of whether the described behaviour constituted stalking or on perceptions of the likelihood of the target of the behaviour experiencing anxiety. However, perpetrator diagnosis did have a significant effect on perceptions of the likelihood of violence and of the perpetrator’s responsibility for their behaviour. Implications for criminal justice outcomes are discussed.